Enhancing learning in business development education through a method for engineering of digital innovation - Murad Huseynli; Udo Bub (Cogent Education)
Academic institutions are keen to integrate cutting-edge, innovative methodologies into curricula, notably through hands-on experiences. This paper introduces a study on a digital innovation engineering methodology applied in the Business Development Laboratory course. The approach provides students with a structured framework to navigate through the innovation process. It enhances the learning experience and bridges theory with practical application. Emphasizing a ‘fail early, fail often’ mentality, the methodology offers valuable feedback and enable students to pivot toward more promising ideas. Adopting a design science research (DSR) approach fosters continuous improvement and contributes to information systems and digital innovation knowledge and encourages to build tangible artifacts. The paper highlights the benefits of the methodology in an educational setting through conducted survey and observation, emphasizing its role in developing digital professionals ready for impactful contributions in the digital era.